2017
DOI: 10.1152/jn.00490.2017
|View full text |Cite
|
Sign up to set email alerts
|

Surface electrodes record and label brain neurons in insects

Abstract: We used suction electrodes to reliably record the activity of identified ascending auditory interneurons from the anterior surface of the brain in crickets. Electrodes were gently attached to the sheath covering the projection area of the ascending interneurons and the ringlike auditory neuropil in the protocerebrum. The specificity and selectivity of the recordings were determined by the precise electrode location, which could easily be changed without causing damage to the tissue. Different nonauditory fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is still not certain if the auditory brain neurons represent individuals or functional types. Surface electrode labeling of the ring-like auditory neuropil reveal three cluster with about 54 cell bodies, which could be linked to auditory processing ( Kostarakos and Hedwig, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is still not certain if the auditory brain neurons represent individuals or functional types. Surface electrode labeling of the ring-like auditory neuropil reveal three cluster with about 54 cell bodies, which could be linked to auditory processing ( Kostarakos and Hedwig, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only does it contain the axonal arborization of the ascending, calling song frequency-sensitive auditory interneuron, AN1, but several local auditory interneurons that have a critical role in pattern recognition also have their arborizations confined to this neuropil region. (Kostarakos and Hedwig 2012 , 2017 ; Schöneich et al 2015 ). The second ascending auditory interneuron, AN2, which is most strongly responsive to auditory frequencies higher than calling song, also has an extensive arborization within the ring neuropil.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have carried out basic investigations on the spectral sensitivity of locusts' phototaxis and visual orientation model. In a study of locusts' visual sensitivity spectrum [3][4][5][6][7][8][9] , Vishnevskaya et al [3] considered that the visual pigments in the retinal cells of a locust's compound eye are sensitive to the spectrum with 430 nm and 515 nm of peak wavelength. Jiang [4] revealed that locusts' screening pigments have two sensitive spectral bands, 400-520 nm and 365-390 nm.…”
Section: Introduction mentioning
confidence: 99%